Corte e cerimoniale di Carlo di Borbone a Napoli - Anna Maria Rao (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2020)
In 1734 Charles of Bourbon's accession to the Neapolitan throne put an end to the Two Sicilies' centuries-old dependency on foreign and non-resident monarchs. Thus a royal court took shape, and shortly thereafter became a matter of admiration to diplomats and foreign travelers, as well as a symbol of reinforcement of the State's authority and autonomy. This volume investigates Charles' and Maria Amalia's court, that has long been neglected by historians, from different points of view: continuity and changes with respect to previous viceregal models and other European models, the symbolic importance of ceremonies and etiquette in creating hierarchies, the architectural scenarios and the plurality of locations (Naples, Capodimonte, Caserta, Carditello, Portici, Persano). Weddings, births, funerals, theatrical performances and archaeological excavations, hunting meetings and secular and religious ceremonies: for the king, all these were occasions to exhibit his majesty and munificence, and to celebrate the union between himself and his subjects. Even bows and hand-kissing could serve to build a society of good manners and to forge a prominent image of the Neapolitan State on the European stage.